THE ANALYSIS OF DISPOSITION EFFECTAND PRICE REVERSAL TAKING UNOBSERVABLE FACTORS INTO CONSIDERATION: WITH SPECIAL REFERENCE TO THE SRI LANKAN STOCK MARKET - Madduma Bandara, Y. M. H. P. (Department of Business Economics, University of Sri Jayewardenepura, 2012)
Disposition Effect, which has been popularized and well documented as one of the various explanations for the persistence of momentum in the returns of the stocks over various time horizons was first documented by Shefrin and Statman (1985). Accordingly, the disposition effect refers to the tendency of investors to realize their profits too early and reluctance to realize their losses that arise out of changes in stock prices. The downward pressure on the prices of winner stocks due to higher growth in trading volume could lead to a price reversal, which ultimately results in losers outperforming winners for a specific time. This price reversal tendency could be influenced by many factors of which some are observable and, some, unobservable. Consideration of observable factors while disregarding those unobservable variables may result in producing biased and counterintuitive estimates by cross sectional and time series analyses. Based on the studies by Cressy and Farag (2009, 2010) this study examines by using Fixed Effects Model which takes unobservable factors into consideration, whether past losers outperform past winners. Using daily data from the Sri Lankan stock market, a sample of 20 stocks that faced a drastic 1 day price change was taken to examine price reversals. Even though cross section and pooled regression results yield insignificant results, fixed effects model strongly supports price reversals of the winning and losing stocks. These results suggest that the unobservable time specific together with firm specific factors play a major role in explaining price reversals in the Sri Lankan stock market.